Digital control of high DC voltage converter based on cockcroft walton voltage multiplier circuit - Muhammad, K.S.; Omar, A.M.; Mekhilef, Saad (2007)
A new method of controlling high DC voltage based on Cockcroft Walton Voltage Multiplier circuit by using digital controller is presented. The digital controller is developed using Complex Programmable Logic Devices (CPLD). The proposed system utilizes a single-phase AC as an input supply. The power switching devices in the controlled bridge are controlled by the multiple-pulse Pulse Width Modulation (PWM) switching technique so as to minimize the low order harmonic present on the AC side of the converter system. A low pass filter is incorporated in the circuit to filter out unwanted harmonics and to give a sinusoidal AC current. A high frequency transformer with 1:1 ratio is incorporated in the design to provide galvanic isolation for better circuit performance and protection. The optimum operation of transformer core in four quadrant of B-H curve is also considered in the proposed converter topology. The laboratory model of the converter is developed and tested. The experimental result is compared with the simulation result.